The rise of the alt-right - Main, Thomas James, 1955- (Brookings Institution Press, 2018)
What is the Alt-Right, and how will it affect America? Donald Trump's election as president in 2016 suddenly brought to prominence a political movement that few in political circles or the mainstream media had paid much attention to: the so-called Alt-Right. Steven Bannon, Trump's campaign manager, was a leading figure in the movement, and the election results seemed to give it a real opportunity to gain some political power. But what is the Alt-Right? Is it a movement, a theory, a trend, or just an unorganized group of people far outside of what used to be the political mainstream in America? Or, could it be all of these things? Why has it suddenly emerged into prominence? What impact is it having on American politics today, and what are the prospects for the Alt-Right in the future?Through careful research and analysis, The Rise of the Alt-Right addresses these and other questions, tracing the movement's history from the founding of modern conservatism in postwar America to the current Trump era. Although the Alt-Right might seem to be just the latest extremist group to arise in the United States-one likely to take its place in the graveyard of its many predecessors-Thomas J. Main analyzes evidence that the Alt-Right is having a greater influence on the American political mainstream than did past extremist tendencies. The Rise of the Alt-Right is thus an important study for anyone interested in the future of American politics and public life.